HomeAid application - Zainul Akramin, Ainul Huda; Rosnan, Suhanah; Lokman Hakim, Amirah Aisyah; Shamsul Mahathir, Nur Aina Maisarah; Arman, Nurul Nadhirah; Hasnan, Siti Nuraishah (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2023)
HomeAid, offers multiple home maintenance services to users including basic housekeeping, plumbing, lawn mowing as well as wiring. This application enticing to users from different generations due to the new added features and its user-friendliness. Target audience comprises people who have the inability to clean and maintain their house. Other instances would be vulnerable individuals such as the elderly who experienced difficulties in performing house chores mainly due to their physical disabilities. Peoples may possess limited knowledge on home maintenance together with the safety considerations. In addition, they might not own suitable equipment to perform the job. Main purpose is to help and assist users who face difficulties in cleaning and maintaining their house. Meanwhile, the second objective is to provide the best home maintenance services to users in a single application. Last objective is to enable users to unwind and enjoy their free time after an exhausting day. This product increases the services offered including basic housekeeping, plumbing, lawn mowing and wiring which are not available and offered by our competitor. In addition, the details of our helpers including their rating and reviews by previous clients can be seen. In addition, we have also included details of their expertise as well as experiences in the field. It is up to the user to complete their cleaning according to their preferences; hence this application considered to be helpful for the user. The HomeAid application is made to assist users in obtaining help to clean and organize their home.